The acute effect of verbal instructions on performance and landing when dropping from different heights: the ground reaction force-time profile of drop vertical jumps in female volleyball athletes - Greca, S. L.; Antonacci, G.; Marinelli, S.; Cifelli, P.; Di Giminiani, R. (Frontiers in Sports and Active Living, 2024)
Introduction: The drop vertical jump (DVJ) is extensively utilized for conditioning and evaluating physical performance, as well as reducing the likelihood of injury by enhancing joint stability through the coactivation of muscles acting on the joint. The execution of DVJ can be controlled by verbal instructions and evaluated by the vertical ground reaction force (vGRF)-time profile.